CSC236H: Introduction to the Theory of Computatoin Homework 1 Solutions 1. Use induction to prove that the following equation holds for all positive integers n: n X k=1 n 1 = . k(k + 1) n+1 Solution. We prove this by induction on n. Base case: Note that for n = 1 both sides of the equation equal 1/2. Inductive hypothesis: Let m ∈ N and suppose the statement is true for n = m − 1, i.e. suppose that m−1 X k=1 1 m−1 = . k(k + 1) m Induction step: Using the inductive hypothesis we have m X k=1 1 k(k + 1) = m−1 X k=1 1 1 + k(k + 1) m(m + 1) m−1 1 + m m(m + 1) (m − 1)(m + 1) + 1 m(m + 1) m . m+1 = = = Therefore the statement is also true for n = m. 2. Use induction to prove 3n < n! for all n > 6 with n ∈ N. Solution. Base case: The claim is made for n > 6. Therefore the base case we need to verify is n = 7. Since 37 = 2187 and 7! = 5040 the statement holds for the base case. Inductive hypothesis: Let m ∈ N be an integer greater than 7 and assume that the statement is true for n = m − 1, i.e. we assume taht 3m−1 < (m − 1)!. Induction step: By the above assumption we have 3m = 3 · 3m−1 < 3 · (m − 1)! by the induction hypothesis < m · (m − 1)! since m > 7 = m! 3. Use induction to prove that every positive integer n ∈ Z+ can be expressed as the product of an odd number and a power of two. In other words, show n = (2k + 1)2p where k ∈ N and p ∈ N. Hint: In the inductive step, break the proof down into one case for even numbers and one case for odd numbers. Solution. Basis: For n = 1, choosing k = 0 and p = 0 ,n = (2 · 0 + 1)20 = 1. Inductive hypothesis: Let m ∈ N with m > 1. Assume the the claim holds for n ∈ {1, . . . , m − 1}, i.e. they can each be written as the product of an odd number and a power of two. Induction step: The number m is either even or odd. 1 • If m is even, then m = 2r for some 1 ≤ r < m. By induction hypothesis, r = (2t + 1)2q for some integers t and q. Thus m = 2r = (2t + 1)2q+1 . In other words, the statement of the lemma holds if we let k = t and p = q + 1. • If m is odd, then m = 2r + 1 for some integer r. But then m = (2k + 1)2p for k = r and p = 0. 4. If you’ve done much graphics programming, you may have used the following two standard trigonometric identities often used to rotate objects: cos(x + y) = cos(x) cos(y) − sin(x) sin(y) sin(x + y) = sin(x) cos(y) + cos(x) sin(y) Using these formulas, prove by induction that for any natural number n and any real number x (cos(x) + i sin(x))n = cos(nx) + i sin(nx) where i is the imaginary unit, i.e. the square root of -1 (in other words i2 = −1). Do not convert this problem to exponential notation and try to solve it in that form. It doesn’t make things simpler and it will confuse us when we grade. Hint: this is not as bad as it looks. If your equations seem very complicated and won’t simplify, look for a mistake in your algebra. Solution. Basis: since the statement is supposed to hold for any natural number, the basis is n = 0 in which case we have (cos(x) + i sin(x))0 = 1, and cos(0 · x) + i sin(0 · x) = cos(0) + sin(0) = 1. Inductive hypothesis: let m ∈ N be a natural number. Assume that the statement of the problem holds for n = m − 1. Induction step: for n = m we have (cos(x) + i sin(x))m = (cos(x) + i sin(x)) · (cos(x) + i sin(x))m−1 = (cos(x) + i sin(x)) · (cos((m − 1)x) + i sin((m − 1)x)) = cos(x) cos((m − 1)x) − sin(x) sin((m − 1)x) + i(sin(x) cos((m − 1)x) + cos(x) sin((m − 1)x)) = cos((m − 1)x + x) + i sin((m − 1)x + x) = cos(mx) + i sin(mx). 2